2022
DOI: 10.3389/fnins.2022.893903
|View full text |Cite
|
Sign up to set email alerts
|

The neurobiology of misophonia and implications for novel, neuroscience-driven interventions

Abstract: Decreased tolerance in response to specific every-day sounds (misophonia) is a serious, debilitating disorder that is gaining rapid recognition within the mental health community. Emerging research findings suggest that misophonia may have a unique neural signature. Specifically, when examining responses to misophonic trigger sounds, differences emerge at a physiological and neural level from potentially overlapping psychopathologies. While these findings are preliminary and in need of replication, they suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 225 publications
0
5
0
Order By: Relevance
“…The supplementary motor area (SMA) properly constitutes a significant portion of the superior frontal gyrus, occupying approximately one-third of its overall territory. 39 The SMA plays a crucial role in planning complex movements and executing deliberate motor actions. Chewing is one such complex movement that requires the intricate coordination of various muscles and structures within the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The supplementary motor area (SMA) properly constitutes a significant portion of the superior frontal gyrus, occupying approximately one-third of its overall territory. 39 The SMA plays a crucial role in planning complex movements and executing deliberate motor actions. Chewing is one such complex movement that requires the intricate coordination of various muscles and structures within the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies have attempted to identify the regions of the brain activated when misophonic sounds are perceived ( Neacsiu et al, 2022 ). A first study carried out based on IRMf showed that misophonic sounds (presented alone, without context) triggered in misophonic subjects exaggerated cerebral responses in the anterior insular cortex.…”
Section: Suggested Mechanisms Of Misophoniamentioning
confidence: 99%
“…Z. J. Williams et al, 2022) reflects difficulties in 'attentional filtering' of these sounds, attributing salience to specific sounds, and/or regulating emotional reactions to distressing sounds (Neacsiu et al, 2022; Z. J. Williams, He, et al, 2021).…”
Section: The Consideration Of Diagnosable Auditory Conditionsmentioning
confidence: 99%